1988
DOI: 10.1901/jaba.1988.21-411
|View full text |Cite
|
Sign up to set email alerts
|

Replacing Maladaptive Speech With Verbal Labeling Responses: An Analysis of Generalized Responding

Abstract: We taught three mentally handicapped students to answer questions with verbal labels and evaluated the generalized effects of this training on their maladaptive speech (e.g., echolalia) and correct responding to untrained questions. The students received cues-pause-point training on an initial question set followed by generalization assessments on a different set in another setting. Probes were conducted on novel questions in three other settings to determine the strength and spread of the generalization effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…These include verbal imitation (as shown by Jason's results) and listener skills (e.g., responding to one's name, orienting towards the speaker). For example, Foxx, Faw, McMorrow, Kyle, and Bittle (1988), Foxx, McMorrow, Davis, andBittle (1987) systematically taught their participants to pause, attend, and respond to prompts following questions. Such interventions should be employed as necessary.…”
Section: Discussionmentioning
confidence: 99%
“…These include verbal imitation (as shown by Jason's results) and listener skills (e.g., responding to one's name, orienting towards the speaker). For example, Foxx, Faw, McMorrow, Kyle, and Bittle (1988), Foxx, McMorrow, Davis, andBittle (1987) systematically taught their participants to pause, attend, and respond to prompts following questions. Such interventions should be employed as necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The basic plan in devising a treatment for echolalia was to develop procedures that reduced the likelihood of echolalic responses and`replaced' them with stimulus appropriate ones. The results of this work have been encouraging (Foxx & Faw, 1990;Foxx et al, 1987Foxx et al, , 1988bFoxx, Faw, McMorrow, Davis, & Bittle, 1988;. For example, some students not only learned appropriate responses to as many as 70 dierent verbal stimuli (i.e., questions and statements) in a total of about 12 hours of training, but also to use the trained responses (i) when persons other than the primary trainer presented the stimuli, (ii) in dierent settings, (iii) when no prompts, feedback or reinforcement were given, and (iv) several years after training (Foxx & Faw, 1990).…”
Section: General Rationale and Characteristics Of Cues±pause±point Lamentioning
confidence: 67%
“…No dear differences in echolalia were apparent between the training and generalization sets, although correct performance was slightly higher on the former. The subjects' correct responding on the generalization sets was gratifying, because no attempt was made in the original studies to facilitate the transfer of stimulus control from the cues to the generalization set questions, whereas this was actively programmed in the training sets (Foxx et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies using cues-pause-point procedures have shown that mentally handicapped individuals can be taught to use their established repertoires of labeling skills to answer questions rather than to echo (McMorrow & Foxx, 1986;McMorrow, Foxx, Faw, & Bittle, 1987) and that these skills generalize to untrained questions (Foxx, Faw, McMorrow, Kyle, & Bittle, 1988). Although these effects were encouraging, no information was provided regarding their durability (e.g., see Foxx, 1990;Foxx, Bittle, & Faw, 1989;Koegel & Rincover, 1977;Lovaas, 1987).…”
mentioning
confidence: 99%
See 1 more Smart Citation